Development of an E-Cigarettes Education and Cessation Program: A South Texas Oral Health Network Study. Issue 1 (January 2021) - Mungia, Rahma; Case, Kathleen; Valerio, Melissa A.; Mendoza, Marissa; Taverna, Melanie; de la Rosa, Elisabeth M.; Nguyen, Thi; Saenz, Gianna; Winkler, Paula; Tsevat, Joel
Electronic cigarette (e-cigarette) use, or vaping, among youth and young adults has become a major public health concern. The prevalence of vaping has grown an astounding 900% among high school students from 2011 to 2015, and e-cigarette use among high school students has increased by 78% from 2017 to 2018, largely due to the rise in popularity of the high-dose nicotine product, JUUL. To date, there are few evidence-based e-cigarette cessation programs. To address this need, the South Texas Oral Health Network collaborated with dental practitioners and community members to conduct focus groups assessing knowledge and awareness of e-cigarette use. Based on this feedback, we developed a dental practitioner–based e-cigarette cessation program. The next step will be to utilize this program in a practice-based research network, a "real-world" practice setting that has the potential to increase the number of dental practitioners who counsel their patients about ecigarettes.